THE EFFECT OF ADVERTISING AND SALES PROMOTION ON CONSUMER BUYING DECISION OF INDOVISION TV CABLE PROVIDER - Nangoy, Christohn Louse; Tumbuan, W.J.F Alfa (Universitas Sam Ratulangi, 2018)
Abstract: On this modern era the development of technology and media communication are rapidly growing and changing. Many things that seen impossible by human in the past has now becomes possible. Current technological developments increasingly dynamic and innovative, so the need for technology of information and communication is very important. There are a lot of improvements of the technology that change the mindset of human. The purpose of this research is to find if advertisement and sales promotion have a significant impact. This research used quantitaitve method. The sample of this research is customer of Indovision TV with total of 75. This research used simple random sampling and the date filled by the questionaire. The result of this research shows that there is a significant effect of Advertisement and Sales Promotion on Consumer Buying Decision. Recommendation is that Indovision should make the sales promotion even more because the demand of Cable TV is really high now, Indovision can add more TV Channel that other cable TV did not have. Indovison should have a national or international artist on their Advertising so it can be more attractive.Â Keywords: advertisement, sales promotion, consumer buying decision